The Effect of Insecticide Concentration of The Active Ingredient Mixture Nitenpyram + Pimetrozin on The Intensity of Attacks By Brown Stem Planthoppers (Nilaparvata lugens) on Rice Plants (Oriza sativa L) Inpari 32 Cultivars - Pramesty, Adji; Wisanggeni, Cahyo; Ramdhani, Muhammad Zeva; Deden, Deden; Dukat, Dukat (Green Publisher Indonesia, 2023)
The issue faced by rice farmers in Cirebon is the brown planthopper pest. Brown planthopper infestations can lead to crop damage of up to 40%, and many farmers experience crop failures. This research aims to determine the effect of the concentration of the active insecticide ingredients Nitenpyram + Pymetrozine in controlling the brown planthopper pest and the yield of rice plants (Oryza sativa L.) of Inpari 32 cultivar. The experimental site was at an altitude of approximately 3 meters above sea level. The experimental design used a randomized group design (RGD). There were 5 levels of insecticide concentration treatments and a control (no treatment), each repeated 5 times, resulting in 25 experimental plots. The treatment levels included A (Nitenpyram + Pymetrozine = 1 g/l), B (Nitenpyram + Pymetrozine = 0.75 g/l), C (Nitenpyram + Pymetrozine = 0.5 g/l), D (Nitenpyram + Pymetrozine = 0.25 g/l), and E (control). The experimental results show that the application of the active ingredient Nitenpyram + Pymetrozine effectively reduces the intensity of brown planthopper and other pest attacks on Inpari 32 rice plants, but it does not affect natural enemies. The Nitenpyram + Pymetrozine active ingredient does not cause harm to the rice plants themselves. Based on the data, the results for all concentration levels are relatively the same. However, there is the most efficient concentration, namely the treatment of the active ingredient Nitenpyram + Pimetrozin 0.25 g/l which is capable of producing dry grain of 12.43 kg/plot or the equivalent of 4.972 tonnes/hectare.